Distribution of FC gamma receptor IIa genotypes among Malay patients with periodontitis - Mohd Ayub, Ayros-Asmawati; Taib, Haslina; Ahmad, Azlina; Mokhtar@Makhtar, Khairani Idah; Zainuddin, Siti LailatulAkmar (SciDoc Publishers, 2020)
To evaluate the distribution of Fc gamma receptor IIa (FcγRIIa) gene polymorphism and its possible association with periodontitis in Malay patients. Materials and Methods: Periodontal parameters were recorded in 53 periodontitis and 65 healthy (control) subjects. Samples for genotype analysis were obtained from the buccal cheek mucosa. The FcγRIIa genotypes were determined via nested polymerase chain reaction by using sequence specific primers. Results: The FcγRIIa R/H131 genotype showed the highest prevalence (56.6% in periodontitis and 50.8% in control) by which the H131 allele was slightly dominant in all subjects (51% in periodontitis and 52% in control). However, no significant association was observed between the periodontal parameters and FcγRIIa genotypes (p>0.05). Conclusion: Within the study limitations, FcγRIIa R/H131 genotype was mostly distributed in Malay subjects. There is no significant association between FcγRIIa gene polymorphisms with periodontitis